Población y vulnerabilidad social ante los efectos del cambio climático en el municipio costero de Guamá. / Population and social vulnerability to the effects of the climate change in the coastal municipality of Guamá. - Aimara Ferrera Bergues; Ofelia Pérez Montero; Osmanys Soler Nariño (Universidad de La Habana, 2020)
The present article aims to study the behavior of the variables population, social vulnerability and impact to climate change in the coastal municipality of Guamá, in the province of Santiago de Cuba, from the sociological perspective of environmental complexity. The qualitative and quantitative method of social research was used. Content analysis techniques were applied to the most important statistical publications and research results on the reference coastal area; and the questionnaire was applied to a sample of 165 inhabitants with a 10% margin of error. The results obtained from the analysis of the environmental complexity conclude that the resident population of the municipality of Guamá, presents a high social vulnerability to the natural dangers aggravated by the impact of the climatic change. They need more information, training, and participation in confronting these dangers in order to raise the perception of risk and build a culture of safety in coastal communities. The municipality's natural and coastal resources do not yet constitute a reference for coastal protection for some of its inhabitants in their proposals for measures to adapt to climate change. / RESUMEN El presente trabajo tiene como objetivo estudiar el comportamiento de las variables población, vulnerabilidad social e impacto al cambio climático en el municipio costero de Guamá, en la provincia de Santiago de Cuba, Cuba, desde la perspectiva sociológica de la complejidad ambiental. Se hizo uso del método cualitativo y cuantitativo de la investigación social. Se aplicaron las técnicas de análisis de contenido a las más importantes publicaciones estadísticas y de resultados de investigación sobre la zona costera de referencia; y el cuestionario a una muestra de 165 habitantes con un margen de error del 10%. Los resultados obtenidos desde el análisis de la complejidad ambiental concluyen que: la población residente del municipio de Guamá presenta una alta vulnerabilidad social ante los peligros naturales agravados por el impacto del cambio climático. Esta necesita de mayor información, capacitación y participación en el enfrentamiento a dichos peligros que le permita elevar la percepción del riesgo y la construcción de una cultura de la seguridad en las comunidades costeras. Los recursos naturales y costeros del municipio aún no constituyen referentes de protección costera para algunos de sus habitantes en sus propuestas de medidas para la adaptación al cambio climático.